WILSON-MIKITY SYNDROME - A RARE INTERSTITIAL PULMONARY DISEASE IN NEONATES - D. Yu. Ovsyannikov; M. A. Belyashova; A. A. Krushelnitskiy; A. A. Avakyan; N. O. Zaytseva; E. A. Degtyaryova (Union of pediatricians of Russia, 2014)
Wilson-Mikity syndrome is an interstitial pulmonary disease of unknown etiology developing in neonatal period and characterized by late oxygen dependence development. The article cites data the possible etiological factors, pathogenesis, pathomorphology, clinical, X-ray and CT presentation of this rare disease. Having analyzed observations of patients with this syndrome (n=61) found in literature from 1960 to 2008, we identified relation of the syndrome's manifestation to age and degree of prematurity and disease outcomes. We present results of our observations of 6 patients with Wilson-Mikity syndrome, including data of high resolution computed tomography.